Penatalaksanaan Fisioterapi Pada Pasien PascaStroke Hemiparase Dextra - Pribadi, Wahyu Rama, Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Background: Stroke is a disorder of the central nervous system due to damage to the circulatory system in the brain. Damage to the central nervous system have resulted in disruption of the motor system in the human body after a stroke takes place. Purpose: To determine the effect of treatment with physiotherapy modalities excercise active, passive excercise and approximation in patients with acute receipt. To determine the effect of passive movement gantle, approximation to the strength and muscle tone. Results: An increase in muscle strength, T0 = 1 to T6 = 2. There is a decrease in range of motion for 6 times evaluation. There is no increase in the value of functional activity for 6 times evaluation. Conclusion: Treatment for 6 times is not enough for stroke patients, stroke patients require therapy handlers who regularly and not short. Need to be evaluated further and during therapy should have no role in helping the recovery of the patient's family. Keywords: stroke, active exercise, passive exercise, aproximasi.